2022
DOI: 10.1021/acs.inorgchem.1c03790
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Formally Copper(III) Nitrite Complex in Proton-Coupled Electron Transfer and Nitration of Phenols

Abstract: A unique high-valent copper nitrite species, LCuNO 2 , was accessed via the reversible one-electron oxidation of [M][LCuNO 2 ] (M = NBu 4 + or PPN + ). The complex LCuNO 2 reacts with 2,4,6-tri-tert-butylphenol via a typical proton-coupled electron transfer (PCET) to yield LCuTHF and the 2,4,6-tri-tert-butylphenoxyl radical. The reaction between LCuNO 2 and 2,4-ditert-butylphenol was more complicated. It yielded two products: the coupled bisphenol product expected from a H-atom abstraction and 2,4-di-tert-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…[39] A recent report demonstrates reactivity of a formal copper(III)-nitrite species towards phenol through proton-coupled-electron-transfer (PCET) pathway. [40] Influenced by the presence of a H-bonding network in the second-coordination-sphere of the T2 site in CuNiR, the design principles of a number of recent NiR models employ a protonresponsive functionalities such as 2-hydroxypyridine, pyridine-2carboxylic acid, and/or 3°amine. [24,41,42] Employing a {[Cu II ](k 2 -O 2 N)} + core supported by a tripodal heteroditopic cryptand (mC), our recent report depicted that {[mC]Cu II (k 2 -O 2 N)}(ClO 4 ) (1-NO 2 ) yields NO through a proton-coupled-electron-transfer (PCET) from substituted phenols (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] A recent report demonstrates reactivity of a formal copper(III)-nitrite species towards phenol through proton-coupled-electron-transfer (PCET) pathway. [40] Influenced by the presence of a H-bonding network in the second-coordination-sphere of the T2 site in CuNiR, the design principles of a number of recent NiR models employ a protonresponsive functionalities such as 2-hydroxypyridine, pyridine-2carboxylic acid, and/or 3°amine. [24,41,42] Employing a {[Cu II ](k 2 -O 2 N)} + core supported by a tripodal heteroditopic cryptand (mC), our recent report depicted that {[mC]Cu II (k 2 -O 2 N)}(ClO 4 ) (1-NO 2 ) yields NO through a proton-coupled-electron-transfer (PCET) from substituted phenols (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Tricopper(II) nitrite complexes also catalyze nitrite reduction by thiol to afford NO and disulfide [39] . A recent report demonstrates reactivity of a formal copper(III)‐nitrite species towards phenol through proton‐coupled‐electron‐transfer (PCET) pathway [40] …”
Section: Introductionmentioning
confidence: 99%
“…Two pathways exist in the CuO/PMS system. One way is high-valent copper-initiated carbon-hydrogen bond oxidation with the generation of small molecules eventually mineralized to CO 2 , which is similar to the intermediates in radical and Fe­(V)-dominated systems. ,, Another pathway for 4-CP degradation is to form phenolic polymers via single-electron transfer (SET) since Cu­(III) is a one-electron oxidant, which may be further mineralized in the CuO/PMS system. ,, …”
Section: Resultsmentioning
confidence: 99%
“…19,56,57 Another pathway for 4-CP degradation is to form phenolic polymers via single-electron transfer (SET) since Cu(III) is a one-electron oxidant, which may be further mineralized in the CuO/PMS system. 49,51,58 The structure−activity relationship for organic degradation in the Cu(III)-mediated CuO/PMS system was also investigated. In the SET mechanism dominated nonradical reaction of PMS activation, the degradation rates of organics depend greatly on the electron-donating ability of organics, 28 which can be described by ionization potential (IP, eV).…”
Section: Cu(iii) Enhances Pms Utilization By Minimizing Its Decomposi...mentioning
confidence: 99%
“…It has been demonstrated recently that metal complexes without bearing activated oxygen atom(s), such as metal-hydroxo and -aqua complexes, are active oxidants in both HAT and OAT reactions, affording oxygenated products. ,, Similarly, McDonald and co-workers have demonstrated that high-valent metal-halide species are highly effective oxidants in activating hydrocarbon C–H bonds to yield hydroxylated or halogenated products . However, different from the metal–oxygen intermediates, such as metal-oxo, -peroxo, and -superoxo complexes, acid effects on the chemical properties of the metal-hydroxo, -aqua, and -halide complexes have been rarely explored previously. , Herein, we report for the first time a large decelerating effect of triflic acid (HOTf) on HAT reactions of [Ni III (PaPy 3 *)] 2+ ( 1 , PaPy 3 * = N , N -bis­(4-methoxy-3,5-dimethyl-2-pyridylmethyl)-amine- N -ethyl-2-pyridine-2-carboxamidate) but a large accelerating effect of HOTf on ET and OAT reactions.…”
Section: Introductionmentioning
confidence: 99%